Approaching conversational humour culturally: A survey of the emerging area of investigation. (July 2017) - Sinkeviciute, Valeria; Dynel, Marta
Abstract: This introductory article gives a state-of-the-art picture of the research on conversational humour in cultural contexts. The most important categories of conversational humour are briefly introduced, followed by an overview of the existing research on conversational humour within and across languages and cultures. The focus is both on topical strands and on the prevalent methodological approaches. The paper closes with a summary of the contributions to this Special Issue.